2015
DOI: 10.1179/2049396714y.0000000108
|View full text |Cite
|
Sign up to set email alerts
|

Work-related accidents among the Iranian population: a time series analysis, 2000–2011

Abstract: Background: Work-related accidents result in human suffering and economic losses and are considered as a major health problem worldwide, especially in the economically developing world. Objectives: To introduce seasonal autoregressive moving average (ARIMA) models for time series analysis of work-related accident data for workers insured by the Iranian Social Security Organization (ISSO) between 2000 and 2011. Methods: In this retrospective study, all insured people experiencing at least one work-related accid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The time-series analysis performed in the present study showed that the incidence of AEBM in health care workers in Brazil followed a stable trend. A similar observation was made in a study conducted in Iran, 20 where a time-series analysis of data for the period of 2000 to 2011 revealed a stable frequency of this type of accident. While other studies have demonstrated a decline in these rates from 1998 to 2008 6 and 1997 to 2009, 15 these studies focused on occupational accidents as a whole rather than AEBM in populations of health care workers.…”
Section: Discussionsupporting
confidence: 83%
“…The time-series analysis performed in the present study showed that the incidence of AEBM in health care workers in Brazil followed a stable trend. A similar observation was made in a study conducted in Iran, 20 where a time-series analysis of data for the period of 2000 to 2011 revealed a stable frequency of this type of accident. While other studies have demonstrated a decline in these rates from 1998 to 2008 6 and 1997 to 2009, 15 these studies focused on occupational accidents as a whole rather than AEBM in populations of health care workers.…”
Section: Discussionsupporting
confidence: 83%
“…Combined costs of accidents at work and occupational diseases in 2004 amounted to 8.2-9.2 billion PLN (0.93-1.04% of gross national product); these estimates, however, did not account for several costs categories, i.e., indirect costs and transfer payments [4]. Accidents at work are determined by a variety of behavioral, organizational, technical and economic factors [5]. Contemporary research concerning the reasons behind these accidents is conducted from 3 perspectives: business cycle, labor market and structural characteristics including for instance the size of a company or capital use intensity.…”
Section: Introductionmentioning
confidence: 99%